1992
DOI: 10.1111/j.1365-2982.1992.tb00096.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of enteral infusion of nutrients on canine intestinal motor‐patterns

Abstract: Little is known on the effects of enteral nutrition on intestinal motor patterns. In dogs, intestinal motility was recorded with multiple extra-luminal strain-gauges. A n elemental diet was infused into the jejunum (0.5-2.5 kcal min-') over 6 h. The elemental diet or dog food were also administered orally for comparison. Iejunal infusion o f the elemental diet stimulated jejunal motility; the motor pattern was characterized by clustered contractions. During enteral feeding, stimulation of jejunal motility was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…In adult pigs, however, the MMC is interrupted when the animal is fed discrete, large meals, but not by ad libitum feeding with the same diet (Bueno and Ruckebusch, 1976). Other research has shown that the caloric load regulates the characteristics of the amplitude of contraction and the duration of the intestinal postprandial pattern in adult pigs (Gregory et al, 1986), dogs (Schang et al, 1978;Schmid et al, 1992) as well as in adult humans (Schönfeld et al, 1998). Furthermore, it was demonstrated in adult dogs that during enteral infusion of low caloric load, MMC persisted, apart from a lengthening of phase II and resulting increase in duration of the MMC cycles; only higher caloric load caused complete disruption of the MMC and appearance of postprandial pattern (Defilippi, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In adult pigs, however, the MMC is interrupted when the animal is fed discrete, large meals, but not by ad libitum feeding with the same diet (Bueno and Ruckebusch, 1976). Other research has shown that the caloric load regulates the characteristics of the amplitude of contraction and the duration of the intestinal postprandial pattern in adult pigs (Gregory et al, 1986), dogs (Schang et al, 1978;Schmid et al, 1992) as well as in adult humans (Schönfeld et al, 1998). Furthermore, it was demonstrated in adult dogs that during enteral infusion of low caloric load, MMC persisted, apart from a lengthening of phase II and resulting increase in duration of the MMC cycles; only higher caloric load caused complete disruption of the MMC and appearance of postprandial pattern (Defilippi, 2003).…”
Section: Introductionmentioning
confidence: 99%